Pembelajaran Smash Permainan Bola Voli : Ujicoba Skala Kecil - Destriana Destriana; Destriani Destriani; Herri Yusfi (Pusat Kajian Pendidikan Olahraga, Kesehatan, dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2021)
The purpose of this study was to test the volleyball drills smash learning technique. It is hoped that this experiment can produce a product that can be used for learning volleyball smash games. The method in this research is R&D at the stage of small-scale field trials with quantitative and qualitative data analysis techniques. The instruments used in this study were observation and questionnaires. This study involved 3 observers and 24 physical education students as research respondents. This research found that 88.9% of students can do the drills smash learning technique and this is also supported by the results of observations made by 3 observers, it was found that an average of 89.4% of students could apply the volleyball learning drills smash technique. This shows that the volleyball drills smash learning technique on small-scale trials can be used and applied to students.